(untitled) (KIUT Publication, 2025)
Against the backdrop of rapid population aging and the increasing prevalence of neurodegenerative diseases such as Alzheimer’s and Parkinson’s, interest in studying the molecular mechanisms underlying these conditions is growing. One of the key directions in modern molecular medicine is epigenetics — the field that examines changes in gene expression without altering the primary structure of DNA. Epigenetic processes, including DNA and RNA methylation, histone modifications, and the involvement of non-coding RNAs, play a crucial role not only in neurodegenerative diseases but also in oncological, metabolic, and psychoneurological disorders. Environmental factors, including pollutants, nutrition, and stress, directly influence the human epigenome, shaping individual disease risk and its transgenerational transmission.